2022
DOI: 10.1007/s11356-022-23086-6
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of a single wild boar population in North Rhine-Westphalia (Germany) to perfluoroalkyl acids

Abstract: Perfluoroalkyl acids (PFAA) are among the leading chemical pollutants in the twenty-first century. Of these, perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS) have been widely detected in a large number of animal and environmental samples. Wild boars accumulate PFAA in their livers, but it has not yet been clarified to what extent wild boars of the same population accumulate different PFAA in their livers or whether any conclusions can be drawn from any differences found in regard to enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…PFAS can also be detected in animals living in forests [124,125]. Studies by the Hessian State Laboratory showed that wild boars are more strongly contaminated than roe deer.…”
Section: Occurrence In the Environmentmentioning
confidence: 99%
“…PFAS can also be detected in animals living in forests [124,125]. Studies by the Hessian State Laboratory showed that wild boars are more strongly contaminated than roe deer.…”
Section: Occurrence In the Environmentmentioning
confidence: 99%
“…Interestingly, previous studies have reported that PFOA and PFOS (as the substances most often used in industry) are the main PFASs, to which humans and animals are exposed, and levels of these two compounds noted in various matrices in humans and wild animals have been higher than levels of other PFASs 37 , 38 , 40 , 41 . Contrary to previous investigations, results obtained in the present study have shown that in bats guano collected from all colonies included into the study the concentration levels of PFBuA, PFPeA, PFHxA, PFHpA were higher than PFOA and PFOS.…”
Section: Discussionmentioning
confidence: 99%